Agronomic biofortification of genetically biofortified wheat genotypes with zinc, selenium, iodine, and iron under field conditions - Ram, Hari; Naeem, Asif; Rashid, Abdul; Kaur, Charanjeet; Ashraf, Muhammad Y.; Sudeep Singh Malik; Aslam, Muhammad; Mavi, Gurvinder S.; Yusuf Tutus; Yazici, Mustafa A.; Govindan, Velu; Cakmak, Ismail (Frontiers Media, 2024)
Inherently low concentrations of zinc (Zn), iron (Fe), iodine (I), and selenium (Se) in wheat (Triticum aestivum L.) grains represent a major cause of micronutrient malnutrition (hidden hunger) in human populations. Genetic biofortification represents a highly useful solution to this problem. However, genetic biofortification alone may not achieve desirable concentrations of micronutrients for human nutrition due to several soil- and plant-related factors. This study investigated the response of genetically biofortified high-Zn wheat genotypes to soil-applied Zn and foliarly applied Zn, I, and Se in India and Pakistan. The effect of soil-applied Zn (at the rate of 50 kg ha−1 as ZnSO4·7H2O) and foliar-applied Zn (0.5% ZnSO4·7H2O), I (0.04% KIO3), Se (0.001% Na2SeO4), and a foliar cocktail (F-CT: combination of the above foliar solutions) on the grain concentrations of Zn, I, Se, and Fe of high-Zn wheat genotypes was investigated in field experiments over 2 years. The predominantly grown local wheat cultivars in both countries were also included as check cultivars. Wheat grain yield was not influenced by the micronutrient treatments at all field locations, except one location in Pakistan where F-CT resulted in increased grain yield. Foliar-applied Zn, I, and Se each significantly enhanced the grain concentration of the respective micronutrients. Combined application of these micronutrients was almost equally effective in enhancing grain Zn, I, and Se, but with a slight reduction in grain yield. Foliar-applied Zn, Zn+I, and F-CT also enhanced grain Fe. In India, high-Zn genotypes exhibited a minor grain yield penalty as compared with the local cultivar, whereas in Pakistan, high-Zn wheat genotypes could not produce grain yield higher than the local cultivar. The study demonstrates that there is a synergism between genetic and agronomic biofortification in enrichment of grains with micronutrients. Foliar Zn spray to Zn-biofortified genotypes provided additional increments in grain Zn of more than 15 mg kg−1. Thus, combining agronomic and genetic strategies will raise grain Zn over 50 mg kg−1. A combination of fertilization practice with plant breeding is strongly recommended to maximize accumulation of micronutrients in food crops and to make significant progress toward resolving the hidden hunger problem in human populations.